Subclinical Cardiac Dysfunction in Childhood Cancer Survivors on 10-Years Follow-Up Correlates With Cumulative Anthracycline Dose and Is Best Detected by Cardiopulmonary Exercise Testing, Circulating Serum Biomarker, Speckle Tracking Echocardiography, and Tissue Doppler Imaging - Cordula Maria Wolf; Barbara Reiner; Barbara Reiner; Andreas Kühn; Alfred Hager; Jan Müller; Jan Müller; Christian Meierhofer; Renate Oberhoffer; Renate Oberhoffer; Peter Ewert; Irene Schmid; et al. (Frontiers Media S.A., 2020)
Background: Survivors of childhood cancer are at risk for anthracycline- and/or radiotherapy-induced cardiotoxicity.Aims: The aim of this study was to assess clinical, laboratory, and imaging parameters of subclinical cardiovascular disease in childhood cancer survivors.Methods: Patients underwent cardiopulmonary exercise test (CPET), laboratory testing, transthoracic echocardiography (TTE) with tissue doppler imaging (TDI) and speckle tracking. A subset of patients also underwent cardiovascular magnetic resonance imaging (CMR). Findings were correlated to cumulative anthracycline and exposure to mediastinal irradiation during cancer treatment. In a subgroup analysis, TTE and CMR findings were compared to data from 40 gender- and age-matched patients with childhood onset hypertrophic cardiomyopathy (HCM).Results: Cardiac evaluation was performed in 79 patients (43 males) at 11.2 ± 4.5 years after cancer treatment. Oncologic diagnosis at a median age of 12.0 years was Hodgkin lymphoma in 20, sarcoma in 17, acute leukemia in 24, relapse leukemia in 10, and others in 8 patients. Cumulative anthracycline dose exceeded 300 mg/m2 in 28 patients. Twenty six patients also received mediastinal irradiation. Decreased peak respiratory oxygen uptake in % predicted on CPET, increased levels of N-terminal pro-brain natriuretic peptide (NTproBNP), increased global longitudinal strain on TTE speckle tracking, and diastolic dysfunction on TDI were the most prominent findings on detailed cardiology follow-up. In contrast to HCM patients, childhood cancer survivors did not show left ventricular hypertrophy (LVPWd z-score median 0.9 vs. 2.8, p < 0.001), hyperdynamic systolic function on TTE (Ejection fraction 62 ± 7 vs. 72 ± 12%, p = 0.001), or fibrotic myocardial changes on CMR (Late gadolinium positive 0/13 vs. 13/36, p = 0.001; extracellular volume fraction 22 ± 2 vs. 28 ± 3, p < 0.001) at time of follow-up. There was no correlation between chest radiation exposure and abnormal cardiac findings. Cumulative anthracycline dose was the only significant independent predictor on multivariate analysis for any cardiovascular abnormality on follow-up (p = 0.036).Conclusion: Increasing cumulative anthracycline dose during cancer treatment correlates with subclinical cardiac dysfunction in childhood cancer survivors best detected by elevated cardiac serum biomarkers, decreased exercise capacity on CPET, and abnormalities on echocardiographic speckle tracking and TDI.